Managing uncertainty in intensive care units: Exploring formal and informal coping practices in a university hospital - Georg Schreyögg; Simone M. Ostermann (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
[Introduction ...] The paper is organized as follows: First, we develop a frame of reference based on a brief overview of the concepts of risk and uncertainty and organizational responses. The second part presents our empirical investigation. We briefly report on the results of our exploratory study and then describe first findings of our main study. In part three we will discuss our findings in the light of modern organizational theory. Part four highlights the limitations of our study and discusses implications for further analysis and theoretical conclusions.
Keywords: 650